Mimicry, Hybridity and Liminality in The Movie Avatar: The Way of Water (A Postcolonial Study) - Andreas, Rino; Sanjaya, Candra Rahmat; Wihastiningrum, Zabrina Damayanti; Putra, Romi Iriandi (Universitas Muhammadiyah Surakarta, 2023)
Film is a medium that describes the relationship between